Innovations in Ultra-Wideband Technologies - Sabban, Albert (IntechOpen, 2021)
This book discusses innovation in ultra-wideband (UWB) technologies and systems. Divided into four sections, the volume introduces UWB technologies and RF modules, examines applications of these systems in areas such as medicine and sports, and discusses the importance of an accurate design of microwave modules and antennas.